EXPLORING TADULAKO UNIVERSITY STUDENTS’ PERSPECTIVES IN USING AI-BASED GRAMMAR TOOLS FOR ACADEMIC WRITING - Faiz Ibrahim; Konder Manurung; Moh. Abraham Akbar Eisenring; Abdul Kamaruddin (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aimed to explore the perspectives of English Education students at Tadulako University toward the use of AI-based grammar tools in academic writing. Employing a qualitative exploratory design, the study involved students from the 2023 cohort who were selected through purposive sampling. Data were collected using a qualitative response questionnaire and semi-structured interviews with five participants. The collected data were analyzed using thematic analysis to identify recurring patterns in students' perceptions, experiences, and challenges. The findings revealed that students generally hold positive perspectives toward AI-based grammar tools such as Grammarly, QuillBot, and ChatGPT, perceiving them as effective in reducing grammatical errors, improving sentence clarity, and enhancing writing organization. Students also reported that consistent engagement with AI feedback increased their awareness of recurring writing mistakes and boosted their confidence when submitting academic assignments. Moreover, AI tools were commonly used during the revision stage, functioning as editing aids rather than primary writing assistants. However, several challenges were also identified, including contextually inaccurate suggestions, confusion arising from excessive feedback options, limited access to premium features, and concerns about over-reliance. These findings suggest that while AI-based grammar tools provide substantial support for writing development, their educational value depends on how critically and responsibly students engage with them. Educators are encouraged to integrate guidance on the reflective use of AI tools in academic writing instruction to promote learner autonomy and prevent dependency.